Fear, indeterminacy, and policy responses - Paymon Khorrami; Fernando Mendo (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2025)
We study the global dynamics of the fully stochastic nonlinear version of the New Keynesian model and analyze the efficacy of various policies as equilibrium selection tools in this context. First, we unveil a new class of equilibria, characterized by selffulfilled beliefs about output volatility in recessions, which no conventional Taylor rule can eliminate. An enriched monetary rule specifically targeting risk premia can restore determinacy but becomes infeasible in the presence of a lower bound to interest rates. Second, and in contrast to monetary policy, the fiscal theory of the price level (FTPL) kills all such self-fulfilling volatility. Our main result that FTPL trims volatile equilibria holds in many contexts, including: under an interest rate peg or active Taylor rule, with any degree of price stickiness (including fully rigid prices), with various types of fiscal rules, and with long-term debt.
Keywords: E30; E40; G01; 330; New Keynesian; Taylor rules; Fiscal Theory of the Price Level; risk premia; sunspot equilibria; sentiment